2000
DOI: 10.1074/jbc.275.10.6813
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Migration of Neurites Is Mediated by Adhesion Site Density and Affinity

Abstract: Three-dimensional neurite outgrowth rates within fibrin matrices that contained variable amounts of RGD peptides were shown to depend on adhesion site density and affinity. Bi-domain peptides with a factor XIIIa substrate in one domain and a RGD sequence in the other domain were covalently incorporated into fibrin gels during coagulation through the action of the transglutaminase factor XIIIa, and the RGD-dependent effect on neurite outgrowth was quantified, employing chick dorsal root ganglia cultured two-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 31 publications
9
111
0
Order By: Relevance
“…Similar to previously published (both experimental and theoretical) reports for cell migration on surfaces (18,32) and within 3D matrices (33)(34)(35)(36) , a biphasic dependence of migration on ligand density was found. In contrast to cell migration across surfaces, 3D cell migration is more complex, as it involves additional cellular strategies to overcome the biophysical resistance of the matrix (37).…”
Section: Discussionsupporting
confidence: 78%
“…Similar to previously published (both experimental and theoretical) reports for cell migration on surfaces (18,32) and within 3D matrices (33)(34)(35)(36) , a biphasic dependence of migration on ligand density was found. In contrast to cell migration across surfaces, 3D cell migration is more complex, as it involves additional cellular strategies to overcome the biophysical resistance of the matrix (37).…”
Section: Discussionsupporting
confidence: 78%
“…Overall, the present findings parallel those of many other systems used to present cellular adhesion ligands to cells and probe the effect of ligand types and bulk densities on cell phenotype. 10,11,18,22,23 It was striking that, in certain experiments, the initial spreading of MC3T3 cells was significantly enhanced as the RGD island spacing increased but the growth rate of the cells was unexpectedly suppressed in parallel (Figure 4). These effects were decoupled from the bulk ligand density in the gel ( Figure 5A).…”
Section: Discussionmentioning
confidence: 96%
“…To do this we conjugated KGF to the peptide (Flc)-LNQEQVSPRKKC, which contains the substrate for factor XIII (NQEQVSP) and can therefore be incorporated into fibrin gels during polymerization. 48,49,56 The first leucine was conjugated to fluorescein to allow quantitation of the bound KGF via fluorescence measurements. The peptide was conjugated to KGF through a cysteine residue that was strategically placed at the end of a highly charged spacer region (RKK).…”
Section: Conjugation Of a Fibrin-binding Peptide To Kgfmentioning
confidence: 99%
“…46,47 In particular, it was recently demonstrated that bi-domain peptides could be used to covalently attach small cell adhesion peptides 48,49 or heparin-binding growth factors, such as nerve growth factor or brain-derived neurotrophic factor, into fibrin gels. 44 For the latter, one domain of the peptide was recognized by factor XIIIa and incorporated into fibrin during polymerization, while the heparin-binding domain immobilized heparin, which in turn interacted with the heparin-binding growth factor.…”
mentioning
confidence: 99%